FACTORS RELATED TO THE INCIDENCE OF ADULT HYPERTENSION IN THE WORKING AREA OF THE SATRIA HEALTH CENTER, TEBING TINGGI CITY, 2023 - Sundari, Ayu Eva; Lia Rosa Veronika Sinaga (Akupun Tour Publisher, 2023)
Background: Hypertension is a disease that has the nickname The Silent Killer, which means a silent killer, where symptoms can vary for each individual. Hypertension is grouped into essential hypertension (no known cause) and secondary hypertension (can be determined by certain symptoms). Purpose: The research objective is to determine the factors associated with the incidence of hypertension in the work area of ​​the Satria Health Center, Tebing Tinggi City in 2023. Method: This research is a quantitative study with a cross-sectional design. The population in the study was 14,684 people. The sampling technique was purposive sampling with the Slovin formula as many as 100 people. Sampling was taken in accordance with the research inclusion criteria using questionnaires and direct blood pressure measurements on respondents. Results: The research results showed that there was a significant relationship between age (0.0001), gender (0.019), working status (0.028), family history of hypertension (0.021) and the incidence of hypertension. Disscusion and Conclusion: relationship between age, gender, working status, family history of hypertension, and the incidence of hypertension. It is recommended that community health centers carry out regular PTM counseling and maximize the role of health cadres.